Factores de riesgo asociados al Síndrome Obstructivo Bronquial en niños menores de 2 años hospitalizados en el servicio de Pediatría del hospital Minsa II – 2 Tarapoto periodo Octubre del 2015 – Marzo del 2016 - Muñoz Rengifo, Yolly Katherine (2016)
The objective of the investigation was to determine the endogenous and exogenous risk factors associated with bronchial obstructive syndrome in children under 2 years of age hospitalized at the Pediatric Service of the MINSA II-2 Tarapoto Hospital. Period October 2015 - March 2016. Qualicuantitative, cross-sectional prospective research. As techniques, the documentary review, interview and survey were used. As a result, 56.1% of the families of the children do smoke and 43.9% do not smoke. 48.8% of the mothers are from the urban area and 51.2 from the rural area. 73.2% of the homes of children hospitalized live between 3 to 5 people and 26.8% live more than 6 people. Concluding that the risk factors that had a significant association with obstructive bronchial syndrome are: Child sex is an endogenous risk factor that is significantly associated with the diagnosis of bronchial obstructive syndrome in children under 2 years of age; Resulting in an X 2 = 7.526 and p = 0.023. Whether or not a family member suffers from asthma as an endogenous risk factor is significantly associated with the diagnosis of bronchial obstruction syndrome in children under 2 years of age; Resulting in an X 2 = 6.533 and p = 0.038